The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/polym11111866
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyl-Terminated Triazine Derivatives Grafted Graphene Oxide for Epoxy Composites: Enhancement of Interfacial and Mechanical Properties

Abstract: An effective approach to the fabrication of progressive epoxy nanocomposites by the incorporation of hydroxyl-terminated dendrimers functionalized graphene oxide (GO-TCT-Tris) is reported. The relationship between surface grafting, chemical construction, morphology, dispersion, and interfacial interaction as well as the corresponding mechanical properties of the composites were studied in detail. It was shown that hydroxyl-terminated triazine derivatives have been resoundingly bonded onto the GO surface throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…UTS, impact strength and impact toughness increased by 62%, 51% and 148% for 0.7 wt% PBI–HPG–rGO/epoxy composite as compared to the neat resin, respectively. Ma et al 130 modified GO using hydroxyl-terminated triazine derivatives (GO–TCT–Tris). Flexural strength and modulus increased by 49% and 16% for 0.1 wt% GO–TCT–Tris/epoxy composite than the neat resin, respectively.…”
Section: D Nanosheet Filled Epoxy Composites: Fabrication and Propertiesmentioning
confidence: 99%
“…UTS, impact strength and impact toughness increased by 62%, 51% and 148% for 0.7 wt% PBI–HPG–rGO/epoxy composite as compared to the neat resin, respectively. Ma et al 130 modified GO using hydroxyl-terminated triazine derivatives (GO–TCT–Tris). Flexural strength and modulus increased by 49% and 16% for 0.1 wt% GO–TCT–Tris/epoxy composite than the neat resin, respectively.…”
Section: D Nanosheet Filled Epoxy Composites: Fabrication and Propertiesmentioning
confidence: 99%
“…Even though chemical modification alters the strong sp 2 hexagonal structure into a weaker sp 3 structure, experimental studies have shown that it can improve the mechanical and other engineering properties of the produced nanocomposite [28][29][30][31][32][33][34]. This improvement is highly governed by the functional group type, molecular configuration, and concentration [35][36][37][38]. Despite the limited number of studies dedicated to investigating the effect of graphene nanoplatelet functionalization, there is a need for a systematic approach to understanding the role of different types of graphene nanoplatelet modification and functionalization on the resulting composite mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…73 The CB and VB edge potentials of BM are about À1.56 and 1.1 V vs. NHE with 2.66 eV of band gap, respectively. For further discussion, the calculated work functions for graphene and g-C 3 N 4 were used according to the reference of Ma et al, 74 which were 4.55 eV and 4.34 eV, respectively. The g-C 3 N 4 exhibited the characteristics of an n-type semiconductor.…”
Section: Functional Properties: Photocatalytic Decomposition Of Metha...mentioning
confidence: 99%